PENGARUH KEPEMIMPINAN DAN KEWIRAUSAHAAN TERHADAP KINERJA UMKM DI KABUPATEN NIAS BARAT - FANE PASKAH GULO (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of leadership and entrepreneurship on the performance of Micro, Small and Medium Enterprises in West Nias Regency. It is undeniable that leadership and entrepreneurship are factors that can affect the performance of a business. Improved leadership and entrepreneurship will have a positive impact on the performance of Micro, Small and Medium Enterprises. The research sample identified 150 Micro, Small and Medium Enterprises in West Nias Regency. The method of collecting information for research is by distributing questionnaires to all Micro, Small and Medium Enterprises owners and employees. Data analysis methods for diagnostic tools, which include descriptive analysis, validity test, reliability test, classical assumption test, and hypothesis testing including T-test and F-test. The research tool used to process and analyze this analytical data is SPSS version 25.0. The results show that leadership has a positive and significant effect on the performance of Micro, Small and Medium Enterprises. Entrepreneurship has a positive and significant effect on the performance of Micro, Small and Medium Enterprises. At the same time, leadership and entrepreneurship are very influential in improving the performance of Micro, Small and Medium Enterprises.